Pathogenic Dynamics During Colony Ontogeny Reinforce Potential Drivers of Termite Eusociality: Mate Assistance and Biparental Care - Cole, Erin L.; Rosengaus, Rebeca B. (Frontiers in Ecology and Evolution, 2019)
As an ecologically dominant taxon, termites appear to be resilient to environmental stressors. However, swarming alates (winged-individuals) encounter a myriad of environmental pressures that drastically reduce the probability of colony foundation. Dispersing alates face high rates of predation, desiccation, nitrogen limitation, and risks of infection, among others. We propose that alates benefit from mate assistance and biparental care to overcome some of these challenges. We assessed whether the bacteria, Serratia marcescens (an ecologically relevant, gram-negative, facultative termite pathogen), negatively affected the growth of newly founded termite colonies. Additionally, we revealed the significance of the king’s presence in improving successful establishment of incipient colonies. Virgin queens of the dampwood termite, Zootermopsis angusticollis, were subjected to one of four treatments: naïve (untreated), or injections with either sterile saline, heat-killed S. marcescens, or a sublethal does of live S. marcescens. Each queen was then paired with a naïve, virgin king. The incipient colonies underwent censuses every four days for 80 days. We estimated survival rates and compared the onset of oviposition and hatching, overall egg production and larval hatching success, all as a function of queen treatment and the presence of a mate. We identified factors that, under pathogenic stress, influenced these fitness-related milestones. Queen infection significantly reduced the number of successfully established colonies. Moreover, both the presence of a king and his mass significantly influenced the queen’s survival, her onset of oviposition, overall egg production, and hatching success. We conclude that termite colonies incur significant fitness costs after a queen suffers an acute infection and that the presence of a king (and his stored resources) may help mitigate the negative effects of a queen’s infection. Pathogenic pressures, combined with the significant role of kings in colony success, appear to reinforce two-parent colony foundation, mate assistance, biparental care, and ultimately the overlap of generations, all of which have been considered preadaptations for eusociality. By studying the fitness consequences of pathogenic stress during the ontogeny of a termite colony, we can infer some of the conditions and pressures under which termite sociality likely emerged.